Diagnosis of respiratory epithelial clearance abnormality in patients suffering from chemo-resistant pulmonary tuberculosis with comorbidity of bronchial mucosa - Raznatovska, O. M.; Khlystun, V. M.; Разнатовська, Олена Миколаївна; Хлистун, Валентин Миколайович; Разнатовская, Е. Н.; Хлыстун, В. Н. (Запорізький державний медичний університет, 2018)
Respiratory epithelial clearance timely and early disorder diagnosis in patients suffering from chemo-resistant pulmonary tuberculosis (CRPTB) concomitant pathology of the bronchial mucosa is an actual problem of modern phthisiology, the solution of which will allow the timely application of rational correction, which will increase the effectiveness of this category treatment among patients. Objective is to investigate the nature and features of respiratory epithelial clearance disorders among patients suffering from CRPTB with comorbidity of the bronchi mucous membrane by using the developed method of these disorders diagnosis. Materials and methods. The respiratory epithelial clearance state diagnosis was carried out among 133 patients with CRPTB at the beginning of the intensive phase of antimycobacterial therapy during fibrobronchoscopy, provided there is a concomitant specific pathology of the mucous membrane (including its combination with non-specific endobronchitis). Average age of patients was 36.5 ± 1.1 years old. There were 89 (66.9 %) men and 44 (33.1 %) women. The tracheobronchial tree diagnostic fibrobronchoscopy with further study of the respiratory epithelial clearance condition among patients suffering from CRPTB was carried out by V. M. Khlystun at Phthisiology and Pulmonology Department of Zaporizhzhia State Medical University in CI Zaporizhzhia Regional Antituberculous Clinical Dispensary. Criteria of patients including into the research: existence of resistance of tuberculosis mycobacteria to anti-mycobacterial drugs in patients with new and repeated cases of tuberculosis, existence of pathology of the mucosa of bronchi confirmed during fiberoptic bronchoscopy. Serious associated diseases (HIV infection/AIDS, diabetes mellitus, etc.) were criteria of exception. The condition of bronchial mucosa was studied under narcotic anaesthesia by fiberoptic bronchoscopes of Olympus (Japan). Pathology of a bronchial tree was described according to classification by M. V. Shesterina, A. N. Kalyuk (1975). Results of the research are processed by modern methods of the analysis using the personal computer with the statistical package Statistica® for Windows 6.0 license program (StatSoft Inc., No. AXXR712 D833214FAN5). Results. There were respiratory epithelial clearance disturbances in 94.7 %, which predominate with the 1st and 2nd stages of mucociliary inefficiency (51.1 % and 37.6 %). There was mucociliary inefficiency dependence on the bronchi mucous membrane pathology nature: the incidence of respiratory epithelial clearance in patients with concomitant bronchial tuberculosis in combination with the nonspecific purulent endobronchitis is 2.4 times higher than in those with concomitant bronchial tuberculosis only (70.7 % vs 29.3 %). The association of nonspecific purulent endobronchitis with concomitant bronchial tuberculosis leads to an increase in the mucociliary inefficiency degree of severity, due to its diffuse localization, where it is diagnosed more often than in the limited one, thus, mucociliary inefficiency of the 2nd stage of severity (64.9 % vs 24.6 %, is 2.6 times more (64.9 % vs 24.6 %) and 4.6 times more in the 3rd stage (16.2 % vs 3.5 %). Conclusions. The proposed method for the diagnosis of mucociliary inefficiency disorders among patients suffering from CRPTB with bronchial mucosa concomitant pathology allows to diagnose mucociliary inefficiency and mucociliary inefficiency dependence on the bronchi mucous membrane pathology nature. Своєчасна та рання діагностика порушень мукоциліарного транспорту у хворих на хіміорезистентний туберкульоз (ХРТБ) легень із супутньою патологією слизової оболонки бронхів – актуальна проблема сучасної фтизіатрії, вирішення якої дасть змогу своєчасно застосувати раціональну корекцію, що підвищить ефективність лікування таких хворих. Мета роботи – вивчити характер та особливості порушень мукоциліарного транспорту у хворих на ХРТБ легень із супутньою патологією слизової оболонки бронхів шляхом застосування розробленого способу діагностики цих порушень. Матеріали та методи. Діагностику стану мукоциліарного транспорту виконали у 133 хворих на ХРТБ легень на початку інтенсивної фази антимікобактеріальної терапії під час фібробронхоскопії за умови наявності супутньої специфічної патології слизової оболонки (у тому числі її поєднання з неспецифічним ендобронхітом). Середній вік хворих становив 36,5 ± 1,1 року. Чоловіків було 89 (66,9 %), жінок – 44 (33,1 %). Діагностичну фібробронхоскопію трахеобронхіального дерева з наступним вивченням стану мукоциліарного транспорту у хворих на ХРТБ легень виконали на клінічній базі кафедри фтизіатрії і пульмонології ЗДМУ в КУ «Запорізький обласний протитуберкульозний диспансер» власноруч В. М. Хлистуном. Критерії залучення пацієнтів у дослідження: наявність резистентності мікобактерій туберкульозу до антимікобактеріальних препаратів, наявність патології слизової оболонки бронхів, що підтверджена під час фібробронхоскопії. Критерії виключення: тяжкі супутні захворювання (ВІЛ-інфекція/СНІД, цукровий діабет тощо). Стан слизової оболонки бронхів вивчали під наркозною анестезією фібробронхоскопом фірми «Olympus» (Японія). Патологію бронхіального дерева описували за класифікацією М. В. Шестериної, А. Н. Калюк (1975). Результати дослідження опрацювали сучасними методами аналізу на персональному комп’ютері з використанням статистичного пакета ліцензійної програми Statistica® for Windows 6.0 (StatSoft Inc., № AXXR712 D833214FAN5). Результати. Запропонований спосіб діагностики порушень мукоциліарного транспорту у хворих на ХРТБ легень із супутньою патологією слизової оболонки бронхів шляхом простого та швидкого у використанні методу, без суттєвих матеріальних і часових витрат, залучення додаткового спеціально навченого персоналу, безпечного для здоров’я пацієнта, безпосереднього ендобронхіального введення у бронхи гепаринізованої крові обстежуваного хворого під час фібробронхоскопії, без побічних реакцій та із запобіганням інфікуванню персоналу хіміорезистентими штамами мікобактерій туберкульозу дав змогу виявити порушення мукоциліарного транспорту в 94,7 %, які були переважно з І та ІІ ступенями мукоциліарної недостатності (51,1 % і 37,6 % відповідно). Встановили залежність мукоциліарної недостатності від характеру патології слизової оболонки бронхів: частота порушення мукоциліарної недостатності у хворих із супутнім туберкульозом бронхів у поєднанні з неспецифічним гнійним ендобронхітом вища у 2,4 раза, ніж в осіб із супутнім лише туберкульозом бронха (70,7 % проти 29,3 %). Приєднання неспецифічного гнійного ендобронхіту до супутнього туберкульозу бронха призводить до збільшення ступеня тяжкості мукоциліарної недостатності шляхом дифузної його локалізації, де у 2,6 раза частіше діагностують, ніж при обмеженому, мукоциліарну недостатність ІІ ступеня тяжкості (64,9 % проти 24,6 %), у 4,6 раза – ІІІ ступеня (16,2 % проти 3,5 %). Висновки. Запропонований спосіб діагностики порушень мукоциліарного транспорту у хворих на ХРТБ легень із супутньою патологією слизової оболонки бронхів дає змогу діагностувати порушення мукоциліарного транспорту та визначити залежність мукоциліарної недостатності від характеру патології слизової оболонки бронхів. Своевременная и ранняя диагностика нарушений мукоцилиарного транспорта у больных химиорезистентным туберкулезом (ХРТБ) легких с сопутствующей патологией слизистой оболочки бронхов является актуальной проблемой современной фтизиатрии, решение которой позволит своевременно применить рациональную коррекцию, что повысит эффективность лечения данной категории больных. Цель работы – изучить характер и особенности нарушений мукоцилиарного транспорта у больных ХРТБ легких с сопутствующей патологией слизистой оболочки бронхов путем применения разработанного способа диагностики этих нарушений. Материалы и методы. Диагностику состояния мукоцилиарного транспорта провели у 133 больных ХРТБ легких в начале интенсивной фазы антимикобактериальной терапии во время фибробронхоскопии при наличии сопутствующей специфической патологии слизистой оболочки (в том числе ее сочетания с неспецифическим эндобронхитом). Средний возраст больных составил 36,5 ± 1,1 года. Мужчин было 89 (66,9 %), женщин – 44 (33,1 %). Диагностическая фибробронхоскопия трахеобронхиального дерева с последующим изучением состояния мукоцилиарного транспорта у больных ХРТБ легких проведена на клинической базе кафедры фтизиатрии и пульмонологии ЗГМУ в КУ «Запорожский областной противотуберкулезный диспансер» собственноручно В. Н. Хлыстуном. Критерии включения пациентов в исследование: наличие резистентности микобактерий туберкулеза к антимикобактериальным препаратам, наличие патологии слизистой оболочки бронхов, подтвержденной при фибробронхоскопии. Критерии исключения: тяжелые сопутствующие заболевания (ВИЧ-инфекция/СПИД, сахарный диабет и др.). Состояние слизистой оболочки бронхов изучали под наркозной анестезией фибробронхоскопом фирмы «Olympus» (Япония). Патологию бронхиального дерева описывали по классификации М. В. Шестериной, А. Н. Калюк (1975). Результаты исследования обработаны современными методами анализа на персональном компьютере с использованием статистического пакета лицензионной программы Statistica® for Windows 6.0 (StatSoft Inc., № AXXR712 D833214FAN5). Результаты. Предложенный способ диагностики нарушений мукоцилиарного транспорта у больных ХРТБ легких с сопутствующей патологией слизистой оболочки бронхов путем простого и быстрого в использовании метода, без существенных материальных и временных затрат, привлечения дополнительного специально обученного персонала, безопасного для здоровья пациента, непосредственного эндобронхиального введения в бронхи гепаринизированной крови обследуемого больного во время проведения фибробронхоскопии, без побочных реакций и с предупреждением инфицирования персонала химиорезистентными штаммами микобактерий туберкулеза позволило диагностировать нарушение мукоцилиарного транспорта в 94,7 %, преимущественно с I и II степенями мукоцилиарной недостаточности (51,1 % и 37,6 % соответственно). Установлена зависимость мукоцилиарной недостаточности от характера патологии слизистой оболочки бронхов: частота нарушения мукоцилиарного транспорта у больных с сопутствующим туберкулезом бронхов в сочетании с неспецифическим гнойным эндобронхитом выше в 2,4 раза, чем у лиц с сопутствующим только туберкулезом бронха (70,7 % против 29,3 %). Присоединение неспецифического гнойного эндобронхита к сопутствующему туберкулезу бронха приводит к нарастанию степени тяжести мукоцилиарной недостаточности за счет диффузной его локализации, где в 2,6 раза чаще диагностируют, чем при ограниченном, мукоцилиарную недостаточность II степени тяжести (64,9 % против 24,6 %), в 4,6 раза – III степени (16,2 % против 3,5 %). Выводы. Предложенный способ диагностики нарушений мукоцилиарного транспорта у больных ХРТБ легких с сопутствующей патологией слизистой оболочки бронхов позволяет диагностировать нарушения мукоцилиарного транспорта и установить зависимость мукоцилиарной недостаточности от характера патологии слизистой оболочки бронхов.
Діагностика порушень мукоциліарного транспорту у хворих на хіміорезистентний туберкульоз легень із супутньою патологією слизової оболонки бронхів
Диагностика нарушений мукоцилиарного транспорта у больных химиорезистентным туберкулезом легких с сопутствующей патологией слизистой оболочки бронхов
Keywords: bronchoscopy; trachea bronchial tree mucosa; chemoresistance tuberculosis; mucociliary transport system; бронхоскопія; трахеобронхіальне дерево; слизова оболонка; хіміорезистентний туберкульоз; мукоциліарна транспортна система; бронхоскопия; трахеобронхиальное дерево; слизистая оболочка; химиорезистентный туберкулез; мукоцилиарная транспортная система